Chitosan and collagen composite for potential application as bone substitute - de Castro, Karine Cappuccio; van de Graaf, Guilherme Maia Mulder; Marques, Rodrigo Fernando Costa [UNESP]; Campos, Maria Gabriela Nogueira (Springer Nature, 2019)
Purpose: Biopolymers, such as chitosan and collagen, have excellent biocompatibility and can be used for bone remodeling. Chitosan and collagen can be crosslinked by glutaraldehyde. The aim of this study was to formulate a chitosan, collagen, and calcium phosphate-based device for potential application as bone substitutes. Methods: The device was synthesized, molded, dried, and characterized. Results: By FTIR, it was possible to observe a characteristic peak relating to the crosslinking of chitosan and collagen. The images of SEM and BET/BJH results showed the presence of apparent and interconnected pores. TG-DSC have shown two temperature ranges for weight loss. Mechanical tests provided an elastic modulus equal to 239.25 ± 78.37 MPa and maximum tension of 4.33 ± 0.95 MPa, which are comparable to some commercial bone substitutes and other similar synthetic devices. Conclusion: The synthesized device showed interconnected pores and surficial porosity, besides thermal stability at physiological temperature, and mechanical properties comparable to spongy bones.
Keywords: Bone tissue; Calcium phosphate; Chitosan; Collagen; Regeneration